2007
DOI: 10.1128/mcb.01307-06
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Mutations in the MDM2 Zinc Finger Domain Disrupt Ribosomal Protein Interaction and Attenuate MDM2-Induced p53 Degradation

Abstract: The p53-inhibitory function of the oncoprotein MDM2 is regulated by a number of MDM2-binding proteins, including ARF and ribosomal proteins L5, L11, and L23, which bind the central acidic domain of MDM2 and inhibit its E3 ubiquitin ligase activity. Various human cancer-associated MDM2 alterations targeting the central acidic domain have been reported, yet the functional significance of these mutations in tumor development has remained unclear. Here, we show that cancer-associated missense mutations targeting M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
149
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 58 publications
9
149
0
Order By: Relevance
“…The zinc finger domain is known to mediate other protein-protein interactions. A recent publication confirms that mutations in the zinc finger domain of the MDM2 oncoprotein disrupts ribosomal protein interaction and attenuates MDM2-induced p53 degradation (Lindstrom et al, 2007). Both the delZF and C308A mutations were unable to associate with Smad4 and cells stably expressing either delZF or C308A regained TGF-␤-induced cell growth inhibition and TGF-␤-responsive promoter activity.…”
Section: V-erba Association With Smad4 Dysregulates Tgf-␤ Signalingmentioning
confidence: 88%
“…The zinc finger domain is known to mediate other protein-protein interactions. A recent publication confirms that mutations in the zinc finger domain of the MDM2 oncoprotein disrupts ribosomal protein interaction and attenuates MDM2-induced p53 degradation (Lindstrom et al, 2007). Both the delZF and C308A mutations were unable to associate with Smad4 and cells stably expressing either delZF or C308A regained TGF-␤-induced cell growth inhibition and TGF-␤-responsive promoter activity.…”
Section: V-erba Association With Smad4 Dysregulates Tgf-␤ Signalingmentioning
confidence: 88%
“…Mutation in the zinc-finger of Mdm2 disrupt the binding of Rpl5 and Rpl11, but not Rpl23, to bypass RP-mediated inhibition of Mdm2 (Lindstrom et al, 2007). In general, most cancers ramp up the production of new ribosomes to support elevated levels of protein synthesis, so in this context, the RP-Mdm2-p53 pathway could have a more prominent role in tumor suppression.…”
Section: Nucleolar Stress and Human Diseasementioning
confidence: 99%
“…Detailed analysis revealed that several RPs require the Mdm2 central zinc finger motif for efficient Mdm2 binding. Interestingly, cancer-associated MDM2 mutations have been reported to affect the central zinc finger motif (4,5) and can specifically disrupt RP binding (6). To study the physiological functions of the RP-Mdm2-p53 pathway, we generated mice carrying a single human cancer-associated phenylalanine substitution at cysteine residue 305, which is structurally critical for the central zinc finger of Mdm2 (Mdm2 C305F ).…”
mentioning
confidence: 99%